Elementary School Students' Learning Styles: Perspective of Creative Thinking Skills - Nur Hidayah; Gunarhadi; Karsono (Universitas Pendidikan Ganesha, 2024)
Learning styles can help students enhance their creative thinking abilities. However, the teacher did not modify the learning style during the learning process, therefore students’ creative thinking abilities did not meet expectations. This study aims to analyze elementary school children's learning styles from the standpoint of creative thinking skills. This is a descriptive quantitative research approach using a survey study design. The sample for this research was fourth-grade elementary school students. The tools used to collect data included tests, questionnaires, and observations. Descriptive statistics were used to analyze the data. According to the findings of this study, children with a visual learning style have high levels of creative thinking. As a result, this study reveals that every kid may develop creative thinking abilities ideally with learning that can adjust to individuals' learning styles. The findings of this study may help to improve students' creative thinking skills and serve as one of the answers for teachers in selecting learning models or approaches based on students' learning styles. Future studies should evaluate the efficacy of strategies or models for improving pupils' creative talents. Aside from that, it is feasible to create media, models, and textbooks to help primary school children strengthen their creative thinking skills.